2021
DOI: 10.1002/ece3.8115
|View full text |Cite
|
Sign up to set email alerts
|

Migration stopover ecology of Cinnamon Teal in western North America

Abstract: Identifying migration routes and fall stopover sites of Cinnamon Teal (Spatula cyanoptera septentrionalium) can provide a spatial guide to management and conservation efforts, and address vulnerabilities in wetland networks that support migratory waterbirds. Using high spatiotemporal resolution GPS-GSM transmitters, we analyzed 61 fall migration tracks across western North America during our three-year study (2017)(2018)(2019). We marked Cinnamon Teal primarily during spring/summer in important breeding and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Presenting explicit hypotheses can provide clarity and precision to research studies, and importantly, is helpful when investigating mechanisms for patterns observed (Betts et al 2021), which is useful when studying the behavior of migratory birds. At the same time, descriptive studies are important for collecting observations and inspiring questions for future research; descriptive studies using these tags have yielded new findings about space used for small bird species, including the location of wintering grounds and stopover sites (e.g., Limiñana et al 2012b; Evens et al 2017; Lei et al 2021; Mackell et al 2021), and previously unknown migration routes (e.g., Allport et al 2018; Ng et al 2018). Many papers that focused on spatial information (hypothesis-driven or not) also discussed temporal aspects of migration, such as timing of departure, duration of migration, and variation between populations in phenology.…”
Section: Discussionmentioning
confidence: 99%
“…Presenting explicit hypotheses can provide clarity and precision to research studies, and importantly, is helpful when investigating mechanisms for patterns observed (Betts et al 2021), which is useful when studying the behavior of migratory birds. At the same time, descriptive studies are important for collecting observations and inspiring questions for future research; descriptive studies using these tags have yielded new findings about space used for small bird species, including the location of wintering grounds and stopover sites (e.g., Limiñana et al 2012b; Evens et al 2017; Lei et al 2021; Mackell et al 2021), and previously unknown migration routes (e.g., Allport et al 2018; Ng et al 2018). Many papers that focused on spatial information (hypothesis-driven or not) also discussed temporal aspects of migration, such as timing of departure, duration of migration, and variation between populations in phenology.…”
Section: Discussionmentioning
confidence: 99%
“…Female mallard and cinnamon teal were found on Grizzly Island SWA nesting fields during summer breeding using standard nest dragging techniques (McLandress et al., 1996 ). Breeding and molting cinnamon teal were also captured at various locations within Oregon, Idaho, Colorado, Nevada, Washington and Utah (Mackell et al., 2021 ). To ensure only adults of appropriate size received GPS transmitters (transmitter weight varied by species from <1% to <5% of body weight, as recommended for birds (Barron et al., 2010 ; Kenward, 2001 )), each individual was assessed for body mass and aged based on feather and molt plumage (Carney, 1992 ).…”
Section: Methodsmentioning
confidence: 99%
“…Social learning (Byholm et al 2022 ), assortative mating (Berthold et al 1992 ), innate and learnt behaviors (Burnside et al 2020 ), large individual variation (Wong et al 2022 ), and the tendency to rush across landscape barriers (Lathouwers et al 2022 ) are characteristic attributes of this species. The conditions for suitable stopover and recuperation sites vary depending on the ecoregion (Herbert et al 2022 ; Mackell et al 2021 ; Schmaljohann et al 2022 ; Wright et al 2018 ). In summary, quail migration is influenced by both biological (internal) and ecological (external) factors.…”
Section: Introductionmentioning
confidence: 99%